Memahami Nilai Spiritual dalam Film Upin-Ipin sebagai Tayangan yang Layak Ditonton Anak Usia 2 - 6 Tahun - Muhammad Lukman Haris Firmansah (Program Studi PGRA, 2018)
Early age is a unique age. Unique value because of how to get information and stimulation process through a unique way of playing and watching entertainment. The entertainmen are in a diverse environment. The chosen entertainer should contain spiritual value. Upin-ipin is one of the entertainment known to have religious values, but whether it contains spiritual value. Religious is not necessarily spirituality, because the concept of religiosity and spirituality is different. This descriptive qualitative research investigates the spiritual value of the Upin-Ipin animated film. The results show that Upin-ipin films are spiritually valuable in some episodes of all episodes aired.